Role of microRNA-210 in human intervertebral disc degeneration - ZHANG, DA-YING (Exp Ther Med, 2016)
The present study aimed to investigate the role of microRNA (miR)-210 in the development of intervertebral disc degeneration (IDD). Human nucleus pulposus (NP) samples were collected from patients with scoliosis and IDD (n=12 each) as the scoliosis control and IDD groups, respectively. The expression levels of miR-210 were detected using reverse-transcription quantitative polymerase chain reaction. In vitro overexpression and knockdown of miR-210 in human NP cells were achieved by transfection of NP cells with lentiviral pre-miR-210 and antagomiR-210, respectively. The protein expression levels of homeobox A9 (HOXA9) were then detected in NP cells with modulated miR-210 using western blot analysis. Flow cytometry with allophycocyanin-Annexin V/7 and 7-aminoactinomycin D staining was also used to detect the proportion of NP cells with modulated miR-210 undergoing apoptosis. The current study revealed that the miR-210 expression was decreased in patients with IDD compared with that of the scoliosis control group (P<0.05). Furthermore, the upregulation of miR-210 with pre-miR-210 led to the repression of HOXA9. The HOXA9 level was significantly lower in these cells compared with that of NP cells treated with a corresponding negative sequence (P<0.05). Knockdown of miR-210 with antagomiR-210 resulted in upregulation of HOXA9 in NP cells, determined as the level of HOXA9 was significantly higher than that of NP cells treated with a negative sequence (P<0.05). The proportion of apoptotic NP cells also significantly decreased following treatment with pre-miR-210 compared with the scoliosis control group (12.1±1.43 vs. 23.8±1.22%, respectively; P<0.05). In conclusion, downregulation of miR-210 may promote Fas-mediated apoptosis in human IDD by regulating the expression of HOXA9. This indicates that miR-210 may be closely associated with the development of IDD and may act as a novel target in IDD treatment.